1995
DOI: 10.1038/nm0495-365
|View full text |Cite
|
Sign up to set email alerts
|

Tau protein directly interacts with the amyloid β-protein precursor: Implications for Alzheimer's disease

Abstract: The simultaneous presence of intracellular neurofibrillary tangles (NFT) and extracellular senile plaques in Alzheimer's disease (AD) suggests that the two lesions could be synergistically interrelated. However, although the main protein components of NFT and senile plaques, tau (tau) and amyloid beta-protein, respectively, are well characterized, the molecular mechanisms responsible for their deposition in lesions are unknown. We demonstrate, using four independent techniques, that tau directly interacts with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 31 publications
1
43
0
Order By: Relevance
“…This distinction between APP and Aβ is important in understanding the molecular pathway of AD. It has previously been shown that tau binds to APP [16], and we showed that tau is necessary for the trafficking of APP to the neuronal surface [11]. In this role, tau facilitates the export of iron as APP stabilizes surface ferroportin, which is the obligate iron export protein [11].…”
Section: Introductionmentioning
confidence: 58%
“…This distinction between APP and Aβ is important in understanding the molecular pathway of AD. It has previously been shown that tau binds to APP [16], and we showed that tau is necessary for the trafficking of APP to the neuronal surface [11]. In this role, tau facilitates the export of iron as APP stabilizes surface ferroportin, which is the obligate iron export protein [11].…”
Section: Introductionmentioning
confidence: 58%
“…Moreover, APP transport was shown to be impaired by elevated tau, suggesting a possible link of the 2 proteins (28,29). Oligomeric A␤ can attach to tau (30,31), causing a rapid dissociation of tau from microtubules and a collapse of axonal structures leading initially to synaptic malfunction and ultimately, neuronal death. Interestingly, A␤ may not only be located to the cell surface but also directly interact with mitochondria (20) as it can be imported into mitochondria via the translocase of the outer membrane (TOM) machinery (32).…”
Section: Discussionmentioning
confidence: 99%
“…Aβ may induce the phosphorylation of tau by: (a) directly interacting with a domain of APP (714-723) [47,125], (b) by inducing tau protein kinase I and subsequently, tau proteins recognised by the antibody Alz-50 [132], (c) as a result of synergisms between Aβ and tau [100,101], or (d) by directly altering the phosphorylated state of tau [23].…”
Section: Key Observations In the Development Of The Amyloid Cascade Hmentioning
confidence: 99%